2013
DOI: 10.1002/pmic.201200443
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun proteomic analysis of the Bombyx mori anterior silk gland: An insight into the biosynthetic fiber spinning process

Abstract: The Bombyx mori anterior silk gland (ASG) is a natural fiber manipulator for the material provided by the middle and posterior silk glands. In view of the significant role of the ASG in the liquid-crystal spinning process, a shotgun proteomics approach was taken to study the relationship between the function of proteins in the silkworm ASG and the spinning mechanism. A total of 1132 proteins with 7647 unique peptides were identified in the ASG dataset including some involved in the cuticle, ion transportation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 25 publications
5
31
0
Order By: Relevance
“…Previous studies have shown that chitin‐binding proteins were involved in the formation of shear force in the anterior silk gland . The chitin and chitin‐binding cuticular proteins inside the anterior silk gland lumen form a extracellular matrix layer to protect the gland cells from being damaged by high mechanical shear of spinning, whereas shear force is important to induce the self‐assembly of silk proteins into fibrils …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that chitin‐binding proteins were involved in the formation of shear force in the anterior silk gland . The chitin and chitin‐binding cuticular proteins inside the anterior silk gland lumen form a extracellular matrix layer to protect the gland cells from being damaged by high mechanical shear of spinning, whereas shear force is important to induce the self‐assembly of silk proteins into fibrils …”
Section: Discussionmentioning
confidence: 99%
“…In the silk gland, the chitin layer is present only in the anterior part, but not in the middle and posterior parts, and is localized between the cell layer and the sericin layer . Recent studies indicated that dozens of cuticular proteins are important components of the chitin layer in the silk gland of the fifth instar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anterior silk gland is the key site for the conformational changes in silk fibroin. Studies have shown that V‐ATPase is highly expressed in the anterior silk gland and spinning duct to maintain a low pH environment, which is beneficial to silk fibrillogenesis (Azuma & Ohta, ; X. Wang et al, ; Yi et al, ). In this study, we found that Baf‐A1 can efficiently inhibit the activity of V‐ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…Silkworm is a model of Lepidoptera . Using the proteomic approach, V‐ATPase has been identified with a high expression level in the spinnerets and anterior silk gland in silkworm by Wang and Yi, respectively (X. Wang, Li, Liu, Xia, & Zhao, ; Yi et al, ). Azuma confirmed that V‐ATPase is a key factor in controlling the acidification in these tissues (Azuma & Ohta, ).…”
Section: Introductionmentioning
confidence: 99%